2018
DOI: 10.3389/fnhum.2017.00654
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of BOLD Signal with Linear and Nonlinear Patterns of EEG in Resting State EEG-Informed fMRI

Abstract: Concurrent EEG and fMRI acquisitions in resting state showed a correlation between EEG power in various bands and spontaneous BOLD fluctuations. However, there is a lack of data on how changes in the complexity of brain dynamics derived from EEG reflect variations in the BOLD signal. The purpose of our study was to correlate both spectral patterns, as linear features of EEG rhythms, and nonlinear EEG dynamic complexity with neuronal activity obtained by fMRI. We examined the relationships between EEG patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 68 publications
(109 reference statements)
3
18
0
Order By: Relevance
“…A total of 10 feature values were calculated for DASM from four electrodes. 3) Correlation (ρ a,b ), where EEG spectral powers are correlated with different regions of the brain that directs attention [14] and was computed as,…”
Section: Feature Extractionmentioning
confidence: 99%
“…A total of 10 feature values were calculated for DASM from four electrodes. 3) Correlation (ρ a,b ), where EEG spectral powers are correlated with different regions of the brain that directs attention [14] and was computed as,…”
Section: Feature Extractionmentioning
confidence: 99%
“…It is important to note that the neural activity we consider here only represents the low-frequency component of the synaptic activity, which the BOLD signal is most sensitive to. This is based on studies showing that the amplitude and power of BOLD are directly related to low-frequency electrical activity as measured by EEG (Lu et al, 2007;He et al, 2008;Portnova et al, 2018). We are currently unable to capture high-frequency neural activity because the processes of neurovascular coupling responsible for the conversion of fast synaptic/spiking responses to slow dynamics remain to be unclear.…”
Section: Approximations and Processes Involved In The Modelmentioning
confidence: 99%
“…Furthermore, the FD was found to be useful in terms of detecting the level of arousal (47). In our previous study, we also observed a significant positive correlation between the FD of the EEG signal and the fMRI BOLD signal in certain regions, including the limbic system (48). Thus, the FD in the control group could be used as a measure of arousal, since it represents a higher level of emotional reactivity and lability than that seen in the patient group.…”
Section: Discussionmentioning
confidence: 78%